(3JKHjJ GeGeI GejQ GdeDefjfs - (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3bGd jMj Hf GdMSjf JKHjJ GeGeI CejQ GdeDefjf Ydi Hf GHj WGdH ef cJGH Gddg YR hLd hef bhd QShd Gddg s
(3BNQgG (B:s
(3acd gPG Gdbhd GdPj aj GdcJGH GdPj de jLO fOkG Cf jaSQ Cfg ef YfO Gddg aEf HWd efg MQa HWd cdg hGf KHJ ef Gddg KHJ Ke Pdc hGdMeO ddg hMOI s
(3hgh GdcJGH GdNGeS Vef eLehYI cJHgG GdgGOjs
(3hPdc eOhf Ydi WQI GdcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs